Environmental impact assessment of green roofs using life cycle assessment - M. G. Rasul; L. K. R. Arutla (Energy Reports, 2020)
The main objective of this study was to analyse the environmental impacts of roof top greenery systems for a building in Sydney, Australia, using the Life Cycle Assessment (LCA). SimaPro software was used for the simulation. The input data for SimaPro on roof barrier, protection layer, drainage layer, filter layer, substrate, plants, etc., were taken from Sydney City Council and relevant literature. The environmental impacts of major pollutants such as Abiotic depletion, Global warming (GWP100), Ozone layer depletion (ODP), Human toxicity, Freshwater aquatic ecotoxicity, Marine aquatic ecotoxicity, Terrestrial ecotoxicity, Photochemical oxidation, Acidification and Eutrophication released from raw materials consumption and operation are compared between green roof and non-green roof. The results indicate that green roofs impact about 3 times positively in the environment compared to non-green roofs. Most of the emissions reductions were found to be in the range of 35% to 83%, however, ozone layer depletion is almost nullified when any of the green roofs are installed. It was also found that environmental impacts of both extensive and intensive green roofs are comparable; however, intensive green roofs perform slightly better and are recommended for urban life systems.
Keywords: 330; Environmental life cycle analysis; Green roof; SimaPro